COMPETITIVENESS ANALYSIS OF INDONESIA'S PROCESSED COCOA EXPORTS - Achmad Tjachja Nugraha; Puspi Eko Wiranthi; Aulia Sekar Arum (AGRIBUSINESS JOURNAL, 2021)
This research is backgrounded by the export value of processed cocoa commodities which fluctuates and tends to increase after the issuance of the Exit Duty Policy by the government. Processed Indonesian cocoa has been widely exported abroad but the quality is still lower than in other cocoa exporting countries because Indonesian cocoa beans are still not widely fermented. This study aims to 1) analyze the trade position of Indonesian cocoa processing in the main export destination country, 2) analyze the structure of the cocoa processed market in the main export destination country, 3) analyze the comparative and competitive competitiveness of Indonesian cocoa processing in the main export destination country. The scope of this study includes processed cocoa with the codes HS 1802, HS 1803, HS 1804, HS 1805, and HS 1806 with each four export destination countries. The data used in this study is secondary data from 2009 to 2018. The results of the Herfindahl Index (HI) test obtained the oligopoly market structure in all destination countries of cocoa skin, cocoa paste (except China), cocoa powder, and cocoa fat in Germany and Australia. The monopolistic market structure is found in all chocolate destination countries, including China (cocoa paste), and the American and Dutch markets (cocoa fat). The result for RCA is that all Indonesian processed cocoa commodities except chocolate in Malaysia and Arabia (RCA values of 0.99 and 0.66 respectively) have a comparative advantage with RCA values that are entirely more than one. The results of the EPD test found that Indonesian cocoa processing was in the Rising Star position in the Philippines (cocoa shells and chocolate), China (cocoa paste), India, and the Philippines (cocoa powder).  Falling Star'sposition is in Malaysia and Germany (cocoa shells), all cocoa paste destination countries except China, all cocoa fat destination countries, and Malaysia (cocoa powder and chocolate). Lost Opportunity’s position in China (cocoa powder) and Thailand (chocolate). Retreat positions are in the markets of South Korea (cocoa shells) and Saudi Arabia (chocolate).